Eksplorasi Potensi Lokal melalui Kokurikuler Berbasis Pendampingan Projek Penguatan Profil Pelajar Pancasila untuk Peningkatan Kompetensi Sosial di Sekolah Dasar di DKI Jakarta - Shahibah Yuliani; Nurul Istiqomah; Nova Scorviana H; Nandi Kurniawan; Budiaman Budiaman (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
The Merdeka Curriculum, which has been in place for over three years, emphasizes the development of students' character and competencies. One of the standout features of this curriculum is the Pancasila Student Profile Strengthening Project (P5), designed to help students embody the values of Pancasila, such as integrity, responsibility, and environmental stewardship. As part of this project, co-curricular activities are allocated up to 30% of the learning time, allowing students to engage in meaningful, real-world applications of their education. This initiative, however, is not yet fully maximized in some schools in DKI Jakarta, despite the city's advantages in terms of educational infrastructure and resources. While Jakarta, as Indonesia's capital, boasts considerable educational potential, it also faces unique environmental challenges, including pollution and waste management issues. These challenges, however, offer opportunities for students to become involved in projects that focus on environmental sustainability, making the P5 project even more relevant. Unfortunately, many teachers in the city are still struggling to design and implement effective P5 modules, which hinders the full impact of the program. Without proper training or access to well-structured project modules, teachers often find it difficult to foster the kind of interdisciplinary and practical learning experiences that the curriculum envisions. To address these gaps, it is essential to focus on strengthening teachers’ competencies in developing and implementing P5 modules through targeted mentoring programs. These programs should include lectures on best practices, interactive discussions that allow teachers to share experiences, question-and-answer sessions to address challenges, and practical exercises in module creation. The ultimate goal is to equip teachers with the skills and knowledge necessary to design modules that incorporate local environmental issues, thus making the P5 project more relevant and impactful for students.